PENGARUH PERSEPSI HARGA, PROMOSI, KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN KOPI KENANGAN TAMINI SQUARE - Benedictus Krisna Setiawan; Sinthon Levi Siahaan (Human Capital Development, 2023)
The purpose of this research is to determine the impact of price perception, promotion, and product quality on customer satisfaction at Kopi Kenangan Tamini Square. Data was collected by distributing questionnaires to visitors. The sampling technique used was purposive sampling, involving 177 respondents in a path analysis. Data processing for this study was conducted using SmartPLS version 3.2.9. The research findings indicate a significant direct influence of price perception on customer satisfaction, with promotion having a significant impact on customer satisfaction as well. Additionally, product quality also shows a significant influence on customer satisfaction.